The study of different types of helicopters's rotor head mechanism and their effectiveness [compact disc] - 313880 Sritharan Nadarajan (Skudai : Universiti Teknologi Malaysia, 2005)
Project paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2005